Unmasking Marlina: psychoanalytic perspectives on women's supremacy and subordination in Indonesian cinema - Setiawan, Bayu; Wulandari, Sri; Ridlo, M. Harun Rosyid (Institut Seni Indonesia Surakarta, 2024)
This research aims to explore the unconscious motivations and character development portrayed in the film